Family Health Nursing: A Response to the Global Health Challenges. (February 2013) - Martin, Paul; Duffy, Tim; Johnston, Brian; Banks, Pauline; Harkess-Murphy, Eileen; Martin, Colin R.
The European Family Health Nursing Project is a revitalized World Health Organization initiative led by the University of the West of Scotland. Partner countries include Armenia, Austria, Germany, Italy, Poland, Portugal, Romania, Slovenia, and Spain. European Union Lifelong Learning funding was received in 2011 to facilitate a consistency of approach in the development of a definition of family health nursing, required core competencies and capabilities, and consequent education and training requirements. Global health challenges have informed the development of the project: increasingly aging populations, the increasing incidence in noncommunicable diseases that are currently the main cause of death, and the significant progress made in the way health systems have developed to meet the demands in relation to access and equality of health services. Governments and policy makers should develop a health workforce based on the principles of teamwork and interdisciplinarity while recognizing the core contribution of the "specialist generalist" role in the primary care setting.